ALGORITM UChETA SMEShchENIYa KAK ZhESTKOGO TsELOGO TREUGOL'NOGO ELEMENTA OBOLOChKI PRI ISPOL'ZOVANII MNOZhITELEY LAGRANZhA - YuRIY VASIL'EVICh KLOChKOV; A P NIKOLAEV; OL'GA VLADIMIROVNA VAKhNINA (Structural Mechanics of Engineering Constructions and Buildings, 2009)
THE ALGORITHM OF THE ACCOUNT OF DISPLACEMENT AS A RIGID WHOLE TRIANGULAR SHELL ELEMENT WITH THE HELP OF LAGRANGE MULTIPLIERS